Current Trend of Artificial Intelligence-Augmented Reality in Science Learning: Systematic Literature Review - Dona Budi Kharisma; Sudirman Sudirman; Firman Edi; Ruth Rize Paas Megahati S (Jurnal Penelitian Pendidikan IPA, 2023)
Technologies enable organizations to support and improve knowledge management practices. First, it will be easier to define augmented and virtual reality concepts to better understand them. Artificial Intelligence technology enables organizations to support and improve knowledge management practices. The research aims to explain the current trend of artificial intelligence-augmented reality in science learning. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. An innovation in educational technology to support learning is the existence of AI technology. Technology may speed up education when used wisely and responsibly. The development of artificial intelligence technology can help pupils become more independent. The teacher does not have to play such a dominant role, but his responsibilities are laid out in the context of offering illumination through significant keywords. The basis for every use of technology for teachers is to continue to prioritize the essence of teaching, namely managing the morale and behavior of students. Â